A mantle- and a lower crust-derived bimodal suite in the Yusufeli (Artvin) area, NE Turkey: trace element and REE evidence for subduction-related rift origin of Early Jurassic Demirkent intrusive complex - Dokuz, A; Tanyolu, E; Genç, S (Springer, 2006)
The Yusufeli area, in the Eastern Black Sea Region of Turkey, contains a crystalline complex that intruded into the Carboniferous metamorphic basement and is composed of two intrusive bodies: a gabbro-diorite and a tonalite-trondhjemite. The mafic body (45-57 wt% SiO2) displays a broad lithological spectrum ranging from plagioclase-cumulate to quartz diorite. Primitive varieties of the body have Mg-number, MgO and Cr contents that are close to those expected for partial melts from mantle peridotite. Data are consistent with the magma generation in an underlying mantle wedge that was depleted in Zr, Nb and Ti, and enriched in large ion lithophile elements (K, Rb, Ba, Th). However, high Al2O3, CaO and generally low Ni (< 65 ppm) contents are not in agreement with the unfractionated mantle-derived primitive magmas and require some Al2O3- and CaO-poor mafic phases, in particular, olivine and orthopyroxene. Absence of orthopyroxene in crystallization sequence, uralitization, and a common appearance of clinopyroxene surrounded by hornblende imply an anhydrous phase fractionated from highly hydrous (5-6%) parent. Geochemical modelling suggests derivation by 15-20% melting of a depleted-lherzolitic mantle. The tonalite-trondhjemite body (58-76 wt% SiO2) ranges in composition from quartz diorite to granodiorite with a low-K calc-alkaline trend. Although LILE- and LREE- enriched characteristics of the primitive samples imply a metasomatic sub-arc mantle for their source region, low MgO, Ni and Cr concentrations rule out direct derivation from the mantle wedge. Also, lack of negative Eu anomalies suggests an unfractionated magma and precludes a differentiation from the diorites of mafic body, which show negative Eu anomalies. Their Na enrichments relative to Ca and K are similar to those of Archean tonalites, trondhjemites and granodiorites and Cenozoic adakites. However, they exhibit important geochemical differences from them, including low-Al (< 15 wt%) contents, unfractionated HREE patterns and evolution towards the higher Y concentrations and lower Sr/Y ratios within the body. All these features are obtained in experimentally produced melts from mafic rocks at low pressures (<= 5 kbar) and also widespread in the rocks of arc where old (Upper Cretaceous or older) oceanic crust is being subducted. Major and REE modelling supports formation of the quartz dioritic parent to the felsic intrusive rocks by 70% partial melting of a primitive gabbroic sample (G694). Therefore, once taking into account the extensional conditions prevailing in the Pontian arc crust in Early Jurassic time, former basic products (gabbros) seem to be the most appropriate source for the tonalite-trondhjemite body. Magmatic emplacement of stratigraphically similar lithologies in the Pulur Massif, just southwest of the Yusufeli, was dated to be 184 Ma by the 40Ar/39Ar method on amphibole, and is compatible with the initiation of Early Jurassic rifting in the region.
Keywords: low-K bimodal suite; trace elements; crystallization conditions; subduction; rifting; emplacement; Demirkent intrusive complex; Yusufeli-Artvin; Eastern Pontides; Turkey